Analisis Pelayanan Bank Syariah Indonesia KCP Medan Juanda - Friska Haliza Siregar; Haris Sugito Saragih; Cita Ayni Putri Silalahi (AGHNIYA : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the service quality of Bank Syariah Indonesia (BSI) Medan Juanda Sub-Branch Office based on the Management Fieldwork Program conducted by students of the Sharia Business Management Study Program. The research applied a descriptive qualitative method with data collected through observation and documentation. The results indicate that services at BSI Medan Juanda are good, reflected in employee friendliness, transaction speed, and the clarity of product information. The implementation of sharia principles is ensured since all banking products are supervised by the Sharia Supervisory Board. However, several challenges were identified, such as long queues during peak hours, limited customer service staff, and low customer understanding of sharia products. Recommendations include adding service staff, optimizing digital services through BSI Mobile, and providing continuous socialization of sharia products. The study concludes that services at BSI Medan Juanda have met sharia service standards, although improvements are still required in efficiency and customer literacy.